The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.52547/ijrr.18.4.841
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and comprehensive analysis of the dose-response characteristics of a morning quality check of a linear accelerator and an important application of accelerator performance prediction

Abstract: Background: This paper aimed to analyze the output constancy of a medical linear accelerator using PTW QUICKCHECK webline and studied the sensitivity of the PTW QUICKCHECK webline . Materials and Methods: The paper statistically analyzed the output doses of 6 MV and 10 MV of photons and 6 MeV, 9 MeV, and 12 MeV of electrons from a medical linear accelerator measured before the daily treatment to assess the output stability of a medical linear accelerator. Some modifications were introduced by artificially alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…An established daily output dose monitoring mechanism and an effective routine (daily/ weekly/ monthly) measurement system should be an essential part of radiation therapy linear accelerator system quality assurance [1,2]. Similar study have been performed elsewhere [9,10,12,14,19,20] where various dosimetric parameters of the linear accelerator were studied with the help of different daily QA equipment. Nicewonger D et.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…An established daily output dose monitoring mechanism and an effective routine (daily/ weekly/ monthly) measurement system should be an essential part of radiation therapy linear accelerator system quality assurance [1,2]. Similar study have been performed elsewhere [9,10,12,14,19,20] where various dosimetric parameters of the linear accelerator were studied with the help of different daily QA equipment. Nicewonger D et.…”
Section: Discussionmentioning
confidence: 86%
“…al [12] and Jiang D. et. al [20] performed the evaluations with PTW QCw for the Varian linear accelerator while our study is performed on a Elekta Synergy linear accelerator. Even though the orientation of some of the graphs were different than that of the referenced studies [12,20], the final results expected from the daily QA equipment is in agreement with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nicewonger et al, (2019) [ 9 ] found the PTW Quick check device to be a suitable tool for daily testing quantitatively and efficient solution qualitatively. D.Jiang et al, (2020) [ 3 ] observed that PTW Quick check device produced fitting linearity and reproducibility when compared with Farmer chamber. Dhoju et al, (2023) [ 10 ] concluded Beam monitorization following quality assurance protocol improves quality of the exposed beam during treatment procedure of patients.…”
Section: Methodsmentioning
confidence: 99%
“…As Binny et al, (2016) [ 2 ] correctly stated, every linac require verification to account for uncertainties in linac’s mechanical positions, focal spot position etc, in this study we can see how two beam matched units show varying parameters for the daily QA. D.Jiang et al, (2020) [ 3 ] could observe the drift in the absolute output for all energies but unable to conclude that the issue was with the monitor chamber until after 200 days of measurements and after intense analysis. A tool is hence required to not only measure the daily QA parameters but also to evaluate them and help to identify the issue if the measurement shows marked deviation.…”
Section: Introductionmentioning
confidence: 99%